SUSUNAN KIMIA DJATI SERTA BERHUNGAN DENGAN TAKSONOMI DAN KATA HANNANJA TERHADAP INSEKTA - Dr. Ir. M . H. SIMATUPANG (BERITA BIOLOGI, 1968)
for investigating the special properties of toakwood,the thorough knowledge of the extractives is required. only 8 years age,merely two extractives of teak were know :secondary calcium phosphate and tectequinone.meanwhile, however,the knowladge has been greatly onlarged some 40 other compounds have been found, the chemical constitution of many of which has been determined The folloiwing extractives were found: 6 new anthraquinones, 5 naphthoquinonos,4 quinonos of still unknown structure, loaf-quinones ,2 nautral compounds with naphthalene rings (pierate formation )very small amounts of fatty oil (below 1%)consisting of 8 different fatty acidst Finally,The terpenoidalcompounds squalene betulic acid, one tiriterpeno C30 H48 O5 and two other terpenoids were found, The dchydronaphthol compounds, tectol and dehydrotecto1,clucidated in their constitution by decomposition and synthesis